ERBB2 and KRAS alterations mediate response to EGFR inhibitors in early stage gallbladder cancer. Issue 8 (8th December 2018) - Iyer, Prajish; Shrikhande, Shailesh V.; Ranjan, Malika; Joshi, Asim; Gardi, Nilesh; Prasad, Ratnam; Dharavath, Bhasker; Thorat, Rahul; Salunkhe, Sameer; Sahoo, Bikram; Chandrani, Pratik; Kore, Hitesh; et al.
Abstract : The uncommonness of gallbladder cancer in the developed world has contributed to the generally poor understanding of the disease. Our integrated analysis of whole exome sequencing, copy number alterations, immunohistochemical, and phospho‐proteome array profiling indicates ERBB2 alterations in 40% early‐stage rare gallbladder tumors, among an ethnically distinct population not studied before, that occurs through overexpression in 24% ( n = 25) and recurrent mutations in 14% tumors ( n = 44); along with co‐occurring KRAS mutation in 7% tumors ( n = 44). We demonstrate that ERBB2 heterodimerizes with EGFR to constitutively activate the ErbB signaling pathway in gallbladder cells. Consistent with this, treatment with ERBB2 ‐specific, EGFR ‐specific shRNA or with a covalent EGFR family inhibitor Afatinib inhibits tumor‐associated characteristics of the gallbladder cancer cells. Furthermore, we observe an in vivo reduction in tumor size of gallbladder xenografts in response to Afatinib is paralleled by a reduction in the amounts of phospho‐ERK, in tumors harboring KRAS (G13D) mutation but not in KRAS (G12V) mutation, supporting an essential role of the ErbB pathway. In overall, besides implicating ERBB2 as an important therapeutic target under neo‐adjuvant or adjuvant settings, we present the first evidence that the presence of KRAS mutations may preclude gallbladder cancer patients to respond to anti‐EGFR treatment, similar to a clinical algorithm commonly practiced to opt for anti‐EGFR treatment in colorectal cancer. Abstract : What's new? This study presents the first genomic landscape of early‐stage gallbladder cancer among an understudied ethnic population. Besides suggesting anti‐EGFR therapy as a therapeutic option based on ERBB2 alteration, the evidence suggests that presence of KRAS (G12V) but not KRAS (G13D) mutation may impede treatment response. The findings could potentially lead to early adoption of a clinical algorithm to treat gallbladder cancer patients under neo‐adjuvant or adjuvant settings similar to the one commonly used for anti‐EGFR treatment in colorectal cancer. Furthermore, the findings rationalize inclusion of gallbladder patients under genomically matched basket clinical trials such as the NCI‐Molecular Analysis for Therapy Choice.